Implementasi Metode Variable Costing Untuk Menentukan Biaya Produksi Pada Perusahaaan Manufaktur - Demas Bani Alfan; Danu Pratama Putra; Fita Fadmawati; Ribangun Bamban Jakaria (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
In the manufacturing industry, competition between companies is an inevitable phenomenon along with the spread of businesses in this field. To maintain competitiveness, making the right management policies, including in the calculation of production costs, is crucial. The determination of production costs must be done carefully in order to provide a balanced profit. This study aims to analyze the company's method of calculating production costs with a variable costing approach. The research design is descriptive with the use of quantitative data through secondary data sources. The results showed that the variable costing approach resulted in a fairly low amount of production costs, namely Rp. 6,165,220,371, compared to the company's original calculation of Rp. 6,271,616,917. Thus, calculating the production budget using the variable costing method can be an effective strategy to face competition in the manufacturing industry.